2004
DOI: 10.1111/j.1432-1033.2004.04270.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuroserpin Portland (Ser52Arg) is trapped as an inactive intermediate that rapidly forms polymers

Abstract: The dementia familial encephalopathy with neuroserpin inclusion bodies (FENIB) is caused by point mutations in the neuroserpin gene. We have shown a correlation between the predicted effect of the mutation and the number of intracerebral inclusions, and an inverse relationship with the age of onset of disease. Our previous work has shown that the intraneuronal inclusions in FENIB result from the sequential interaction between the reactive centre loop of one neuroserpin molecule with b-sheet A of the next. We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
73
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(78 citation statements)
references
References 33 publications
(53 reference statements)
5
73
0
Order By: Relevance
“…Six mutations have now been described that underlie FENIB [48][49][50]. We have assessed a range of mutants of different severity in purified recombinant protein, cell, fly, worm and mouse models of disease [48,[51][52][53][54][55][56][57]. The data show a direct relationship between the severity of the mutation, the rate of polymer formation and the severity of the associated dementia.…”
Section: Polymers and The Serpinopathiesmentioning
confidence: 99%
“…Six mutations have now been described that underlie FENIB [48][49][50]. We have assessed a range of mutants of different severity in purified recombinant protein, cell, fly, worm and mouse models of disease [48,[51][52][53][54][55][56][57]. The data show a direct relationship between the severity of the mutation, the rate of polymer formation and the severity of the associated dementia.…”
Section: Polymers and The Serpinopathiesmentioning
confidence: 99%
“…This replacement of a consistently conserved residue in the shutter region resulted in large inclusions with affected family members dying by age 20 years. 83 The role of polymerisation in disease is supported in our demonstration that recombinant Ser49Pro neuroserpin has a greatly accelerated rate of polymerisation when compared to the wild type protein, [84][85][86] and that Ser52Arg, which causes a more severe clinical phenotype, polymerises even more rapidly. 85 The cellular handling of neuroserpin has been assessed by transiently transfecting COS cells with wildtype neuroserpin and mutants of neuroserpin that cause FENIB (Fig 5).…”
Section: Polymers Of Neuroserpin and The Dementia Familial Encephalopmentioning
confidence: 99%
“…83 The role of polymerisation in disease is supported in our demonstration that recombinant Ser49Pro neuroserpin has a greatly accelerated rate of polymerisation when compared to the wild type protein, [84][85][86] and that Ser52Arg, which causes a more severe clinical phenotype, polymerises even more rapidly. 85 The cellular handling of neuroserpin has been assessed by transiently transfecting COS cells with wildtype neuroserpin and mutants of neuroserpin that cause FENIB (Fig 5). The most striking feature of the cell model is the retention of Syracuse (Ser49Pro) and Portland (Ser52Arg) neuroserpin as intracellular aggregates composed of polymers of mutant neuroserpin, similar to the loop-sheet polymers of mutant neuroserpin that can be isolated from the brains of individuals affected by FENIB.…”
Section: Polymers Of Neuroserpin and The Dementia Familial Encephalopmentioning
confidence: 99%
“…[17][18][19][20][21] Our previous work has shown that polymers of neuroserpin result from the sequential linkage between the reactive center loop of one molecule and b-sheet A of another. 7,22 However, it has recently been proposed that such polymers are formed by a b-hairpin linkage between not only the reactive center loop but also s5A inserting into b-sheet A of another molecule. 23 It is these polymers of neuroserpin that aggregate to form the cortical and subcortical periodic acid-Schiff-positive Collin's bodies that are the hallmark of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…17,18,[24][25][26] There is a clear correlation between genotype and phenotype that can be explained on the rate of polymerization. 7,[18][19][20]22 Those mutants that polymerize most rapidly are associated with the greatest number of cerebral inclusions and the earliest age of onset of disease. Neuroserpin can also be inactivated by intramolecular loop insertion to form a latent conformer that has also been isolated from the brains of individuals with FENIB.…”
Section: Introductionmentioning
confidence: 99%